Translation and adaptation of child and adolescent mindfulness measurement into Bahasa version - Sarah Aurelia Saragih; Fitri Ariyanti Abidin (International Journal of Public Health Science (IJPHS), 2022)
The child and adolescent mindfulness measurement (CAMM) is a self-report instrument assessing the ability of mindfulness in adolescents. This assessment is widely used in measuring the effectiveness of mindfulness intervention in children and adolescents. This study aimed to validate the translated Bahasa version of the CAMM. We used international test commission (ITC) guidelines with six steps in the adaptation process. After forward-backward transltion procedure, the participants were 207 adolescents aged 10-17 years (M=15, 00, SD=1.890; girls=130, boys=77). Internal consistency and factor analysis are used to measure the reliability and validity. Investigation of internal consistency Cronbach Coefficient Alpha yielded satisfactory results (.767). Results from confirmatory factor analysis supported the original one-factor model with 2(df=34, p=.088), goodness of fit index (GFI)=.985, comparative fit index (CFI)=.974.). In sum, the Bahasa version of the CAMM can be successfully used for assessment and evaluation of the effect of mindfulness intervention in the Bahasa adolescents' population.